THE DISCOVERY OF ISLAMIC LAW WITH THE TURAS BOOKS: Method Development - yazid, afthon (MAQASHID, 2023)
The dynamics of fiqh that occurred at 2nd H, gave rise to the process of transitioning Islamic law from the form of ijtihad based on the the companions to a scientific and measurable process. Its maintained from Four Imams who codified the results of their legal thoughts in the books of fiqh. The Four Imams and their books could be define in turas books or classical books, have difference thought during determine an ijtihad. This study aims to explain the development method of finding legal sources in turas books based on madzahib al arba'ah scholars. The researchers conducted a library study with a descriptive analysis approach, collected sources, verified, and interpreted in detail. The results showed that in determining the law, the scholars of the mahdhhab put forward their textual and contextual method. The result of the textual law , determined by the Qur'an and hadith, but does not leave the contextually which is ar-rayu. The theory and methodology of the discovery of the law of madzahib scholars are broadly the same. Its using Qur'an, sunnah, ijma' and qiyas. However, in the practice of developing qiyas methodology, scholars of the madhhab have differing in opinion, such as use the method of istihsan, urf, maslahah mursalah, atsar ahlu medina and hadith mursal.